Therapists’ experiences with mentalization-based treatment for avoidant personality disorder - Pettersen, Mona S. (European Journal for Qualitative Research in Psychotherapy, 2021)
Recent research points to significant mentalizing difficulties in individuals with avoidant personality disorder (AvPD). A mentalization-based approach in psychotherapy with avoidant patients is emerging. The aim of this study is to contribute to an understanding of the therapeutic issues such work might entail with our research questions being: a) What are therapists’ experiences of using mentalization-based treatment (MBT) to treat patients with an AvPD diagnosis? and b) What do therapists perceive as therapeutic challenges when conducting MBT with avoidant patients? Semi-structured, in-depth interviews were conducted with six therapists from a MBT team treating patients with AvPD. The data were analyzed using thematic analysis. Two main themes emerged. The first ‘Scarcity of explicit personal narratives’ encompasses ‘Engaging the withdrawn patient’ and ‘Capitalizing on the treatment structure’. The second main theme – ‘On being a patient’ - incorporates ‘Stimulating but emotionally challenging work’ and ‘Making use of experience with other therapeutic approaches’. Participants’ responses about their experience suggests that MBT targets much of the AvPD core pathology. The use of some techniques, however, warrants active consideration, and there may be a need to adjust MBT treatment for use with AvPD patients. Our study reveals more nuances in therapists’ emotional reactions than earlier reported. Future studies should investigate the effect of MBT on AvPD patients and examine treatment processes and interventions that may facilitate change.